Character, Choice and Criminal Responsibility - Mousourakis, George (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1998)
This paper examines the issue of criminal responsibility and the role of legal excuses from two theoretical viewpoints : the character theory and the choice theory of responsibility. The character theory claims that the moral assessment of an offender's character is a necessary prerequisite of criminal liability and punishment. Legal excuses preclude the attribution of moral and legal blame because, by negating voluntariness, they block the inference from a wrongful act to a flawed character. The choice theory, on the other hand, claims that criminal responsibility pertains to the voluntary violation of the law rather than to the doing of an immoral act as such. For the choice theorist criminal responsibility is concerned with choices rather than with character traits. From this point of view, excuses are taken to preclude criminal liability because, when these conditions are present, the actor does not have sufficient capacity or a fair opportunity to choose to act according to law. The paper concludes that the character theory, by placing the emphasis on those character traits that motivate a person's choices offers a better basis for understanding the moral significance of human actions and for explaining and justifying the attribution of criminal responsibility and punishment.